Destination marketing through networks - Königsson, Veronica; Stark, Sara (2009)
The purpose we established for our thesis was to examine the process of marketing a town as a single unit and the use of networks. The appointed research strategy was a case study and we conducted interviews with destination marketing organizations and companies in the towns of Luleå and Piteå. The empirical data that was gathered from the interviews was then compared to previous studies and literature regarding the subject of destination marketing to see if there were any similarities and/or differences. The results of our study showed that much focus is directed on communicating a positive image of destinations through marketing activities. Furthermore, tourism actors within a destination work with networks in order to market the destination as a single unit: to do this successfully the different relationships within the network has to be functioning and the members need to work towards a mutual goal in order to attract as many tourists/visitors as possible to the destination. Validerat; 20101217 (root)